2020
DOI: 10.31033/ijrasb.7.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate and Antibiotic Sensitivity Effect of Some Natural and Petroleum Based Materials on Staphylococcus aureus

Abstract: Numerous bacteria expose to different materials every day. Bacterial genome mainly composed of a single double-stranded circular DNA molecule, which can easily undergo changes or mutations upon the exposure to many substances. The aim of this study was to evaluate the mutagenic effect in term of growth rate and antibiotic sensitivity of some natural and petroleum based materials on Staphylococcus aureus. Exposure to each of Bunsen and acetone lower the growth rate of bacterial cells compared to diesel and engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Most studies, such as Kalemelawa et al (2012) and Mosa et al (2015) focus on the good side of naturally occurring products and ignore the potential lousy side related to a human directly or indirectly. Therefore, more microbiological studies regarding the use of natural coagulants need to be done (Yahya, Alfallous, et al, 2020).…”
Section: Challenges and Propositions Of Using Bio Coagulants In Water...mentioning
confidence: 99%
“…Most studies, such as Kalemelawa et al (2012) and Mosa et al (2015) focus on the good side of naturally occurring products and ignore the potential lousy side related to a human directly or indirectly. Therefore, more microbiological studies regarding the use of natural coagulants need to be done (Yahya, Alfallous, et al, 2020).…”
Section: Challenges and Propositions Of Using Bio Coagulants In Water...mentioning
confidence: 99%
“…In different study, Arshad and Imran [34] evaluated the effect of fluoride-contaminated drinking water consumption in a rural population of Pakistan on the arenicolids and skeletal/dental fluorosis, and concluded that the consumption of high amounts of fluoride can lead to serious health issues. Nitrate (NO3) and nitrites (NO2) are another two parameters naturally found in water [35], the reduction of nitrate to nitrite tern it toxic to human health [36]. It has been reported that nitrite involve in the oxidation of hemoglobin and transform it to met-haemoglobin, a modified compound which is unable to transport oxygen to the cells and tissues [37].…”
Section: Physico-chemical Contamination Of Drinking Watermentioning
confidence: 99%
“…The use of plastic bottles to expose the water to sunlight, which causes elevation in water temperature, raises health concerns about the potential generation of photoproducts or migration of organic compound from the plastic bottles to treated water, which have been linked with many chronic and genetic disorders [143,144]. A limited number of research studies assessed the adverse health effects and the potential toxicity of consuming the water from SODIS process [145,146]. The Ames test was carried out to assess the potential cytotoxicity of the water resulting from the SODIS process [147,148].…”
Section: Leaching In Plastic Bottles and Potential Adverse Health Effectsmentioning
confidence: 99%